The Effect of Customers' Satisfaction towards Customer Loyalty among Mobile Telecomunication Providers in Malaysia - Sarina, Ismail (2009)
The purpose of this study is to understand the effect between customer satisfaction and customer loyalty in the Malaysian mobile telecommunication services. This sector is highly competitive as new players coming in, with aggressive price offering, high promotion, better network quality and great customer service. 157 respondents participated in this study. Out of this five variable tested (Service Quality, Pricing, Switching Cost, and Brand Image) it is found that Responsiveness and Brand Image have a positive relationship on Customer Loyalty. The present study has its own limitation since this research is only conducted in Penang area. Therefore the finding of the study is unable to be generalize for the whole population of hand phone users in Malaysia as the sample size is considered small. In conclusion service providers must be able to understand the effect between customer satisfaction and customer loyal. It will be a great challenge for the service providers in preparing their strategic plan in maintaining customer loyalty, and at the same time expending their customer base.